2019
DOI: 10.3139/120.111292
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the microstructure of dissimilar welds in duplex stainless steel and low alloyed steel

Abstract: The chemical and microstructural heterogeneities of arc welded joints of duplex stainless steel (X2CrNiMoN22-5-3) and chromium-molybdenum (13CrMo4-5) low alloy steel have been investigated. Rutile coated electrodes containing chromium and molybdenum amounts similar to that of duplex stainless steel but with a higher nickel content have been selected for the manual welding of the joints. The higher nickel content has been chosen, since nickel promotes the formation of austenite and induces an approximately equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…They found that the highest hardness value is measured in the narrow zone close to the fusion zone, where there were hard micro-constituents, and which were formed by the migration of carbon from the HSLA side to this narrow zone. Mitelea et al [15] studied the chemical and microstructural heterogeneities of arc welded joints of duplex stainless steel (X2CrNiMoN22-5-3) and low alloy steel (13CrMo4-5).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the highest hardness value is measured in the narrow zone close to the fusion zone, where there were hard micro-constituents, and which were formed by the migration of carbon from the HSLA side to this narrow zone. Mitelea et al [15] studied the chemical and microstructural heterogeneities of arc welded joints of duplex stainless steel (X2CrNiMoN22-5-3) and low alloy steel (13CrMo4-5).…”
Section: Introductionmentioning
confidence: 99%
“…The chromium-molybdenum steel 13CrMo4-5 [6] is commonly used in the energy industry [7] for the construction of critical infrastructure elements, e.g., as a material for steam pipelines [8], due to its favorable mechanical properties [9]. Therefore, the creep resistance or corrosion resistance of this type of steel is extensively tested, taking into account various operating conditions, such as temperature, pressure, or environment [9].…”
Section: Introductionmentioning
confidence: 99%